Who Contributes to the Provision of Public Goods at the Community Level? The Case of Potable Water in Ghana. (November 2016) - Useche, Pilar
Abstract : This article offers an analytical framework to explain participation in the provision of drinking water in communities in Ghana along with empirical evidence of the individual factors that influence this provision. Framed in the context of the debate about the devolution of responsibilities from the government to the users of public goods to increase management efficiency and sustainability, the study analyzes how individuals respond to potable water participation activities. Distinguishing activities by the type of participation incentives they offer, the study finds that social exclusion is more likely in activities that lack effort complementarities and which have larger impacts on output allocation. Appropriation of social benefits is found to determine participation more strongly than the appropriation of the natural resource itself.